Analisis Kinerja Keuangan Perusahaan Multinasional Pasca Akuisisi (Studi Pada Perusahaan Pengakuisisi yang Terdaftar di BEI Periode Tahun 2010 -2012) - Petrus Fransiscus (Fakultas Ilmu Administrasi Universitas Brawijaya, 2015)
This study aims investigate the effect of the acquisition on the company's performance. This study is quantitative in nature, employing the use of secondary data with statistical analysis. The population utilized in this study were financial ratios of the five companies listed on the Indonesian Stock Exchange. Paired Sample T-Test was utilized as mean of statistical analysis. The variables in this research includes : Current Ratio, Debt to Equity Ratio, Debt Ratio, Total Asset Turnover Ratio, Return on Equity, Return in Investment, Operating Profit Margin, Net Profit Margin. The finding of this study were this study found gained eight financial ratios studied by using different test, five of them did not show significant results, because the value of the ratio indicated a better time prior tothe acquisition compared to afte rthe acquisition. Debt to EquityRatio, Return on Equity and Debt ratio is the ratio of the three out of eight showed asignificant effect after the acquisition. Keywords : Acquisitions, Corporate Financial Performance, Corporate Financial Ratios Current Ratio, Debt to Equity Ratio, Debt Ratio, Total Asset turnover Ratio, Return on Equity, Return in investment, Operating Profit Margin, Net Profit Margin ABSTRAK Penelitian ini bertujuan mengetahui pengaruh akuisisi terhadap kinerja perusahaan. Penelitian ini bersifat kuantitatif, menggunakan data sekunder dengan analisis statistik. Populasi yang digunakan dalam penelitian ini adalah rasho keuangan dari lima perusahaan yang terdaftar di Bursa Efek Indonesia. Paired Sample T-Test digunakan sebagai analisis rata-rata statistik. Variabel dalam penelitian ini meliputi: Current Ratio, Debt to Equity Ratio, Debt Ratio, Total Asset Turnover Ratio, Return on Equity, Return in Investment, Operating Profit Margin, Net Profit Margin. Temuan dari penelitian ini adalah delapan rasio keuangan dipelajari dengan menggunakan uji beda, lima di antaranya tidak menunjukkan hasil yang signifikan, karena nilai rasio menunjukkan yang lebih baik sebelum akuisisi dibandingkan dengan setelah akuisisi. Debt to Equity Ratio, Return on Equity dan rasio utang adalah rasio tiga dari delapan menunjukkan dampak yang signifikan setelah akuisisi. Kata Kunci : Akuisisi, Kinerja Keuangan Perusahaan, Rasio Keuangan Perusahaan, Current Ratio, Debt to Equity Ratio, Debt Ratio, Total Asset turnover Ratio, Return on Equity, Return in investment, Operating Profit Margin, Net Profit Margin